2021
DOI: 10.1039/d0ob02279a
|View full text |Cite
|
Sign up to set email alerts
|

Facile access to [1,2]-oxazine derivatives via annulations of aminoxy-tethered 1,7-enynes

Abstract: Highly diastereoselective construction of functionalized cyclopenta[d][1,2]oxazines is achieved from 1-aryl propargyl alcohols via sequential oxyamination/annulation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In 2021, an efficient Ru‐catalyzed ring‐closing enyne metathesis reaction of linear N ‐ O tethered 1,7‐enynes has been disclosed by the Punna group (Scheme 53). [69] The annulation protocol, which occurred in the presence of Grubbs‐(II) (5 mol%) in toluene, afforded a direct approach to access structurally diverse 1,2‐oxazines in good to excellent yields. This strategy featured the advantages of good functional group compatibility, high atom economy, and gram‐scale capacity.…”
Section: Transition Metal‐catalyzed Reaction Of 17‐enynesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, an efficient Ru‐catalyzed ring‐closing enyne metathesis reaction of linear N ‐ O tethered 1,7‐enynes has been disclosed by the Punna group (Scheme 53). [69] The annulation protocol, which occurred in the presence of Grubbs‐(II) (5 mol%) in toluene, afforded a direct approach to access structurally diverse 1,2‐oxazines in good to excellent yields. This strategy featured the advantages of good functional group compatibility, high atom economy, and gram‐scale capacity.…”
Section: Transition Metal‐catalyzed Reaction Of 17‐enynesmentioning
confidence: 99%
“…In 2021, the Punna and co‐authors reported a direct and novel protocol for the construction of vinylated‐[1,2]oxazines in the presence of Co 2 (CO) 8 in DCE at 80 °C for 12 h (Scheme 59). [75] The cobalt‐catalyzed protocol proceeded through a sequential oxyamination and Pauson‐Khand reaction sequences, leading to the functionalized cyclopenta[ d ][1,2] oxazines in good yields. It is worth noting that the raw material aminoxy‐tethered 1,7‐enynes were synthesized from propargyl alcohols.…”
Section: Transition Metal‐catalyzed Reaction Of 17‐enynesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2-Oxazines and their benzo-fused derivatives are embedded in many drugs and bioactive natural products. Their synthetic strategies, which are used as intermediates in synthesis due to their biological potential, have been comprehensively reported [ 1 , 2 , 3 , 4 , 5 , 6 ]. Analogues of 1,2-oxazine, peri- annelated to naphthalene, are not abundant in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Analogues of 1,2-oxazine, peri- annelated to naphthalene, are not abundant in the literature. The first naphtho[1,8- de ][ 1 , 2 ]oxazine to be synthesized was produced by the cyclodehydration of 6,6′,7,7′-tetramethoxygossypol dioxime [ 7 ]. Analogous reactions produced more derivatives [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%